Potensi Pasar Tradisional dalam Peningkatan Ekonomi Masyarakat - Syukria, Alfi (SAFE-Network, 2023)
Traditional markets are markets that play an important role in promoting economic growth in Indonesia. The existence of this traditional market is very helpful, not only for the local or central government but also for the people who depend on their trading activities for the welfare of their lives, be it traders, buyers, butchers and so on. The formulation of the problem in this study is whether the Sungai Sariak traditional market has the potential to improve the economy of the VII Koto Sungai Sariak community. The purpose of this study is to find out that the Sungai Sariak traditional market has the potential to improve the economy of the people of Kecamatan VII Koto Sungai Sariak. From the research results it can be seen that the potential of this traditional market has a very positive impact on improving the community's economy in fulfilling all economic activities in the form of buying and selling transactions between traders and buyers so as to create prosperity among the community, especially District VII Koto Sungai Sariak and the surrounding community. The conclusion from this study is that traditional markets have a major influence on the livelihood systems of the surrounding communities. Sungai Sariak Market is a means to carry out economic activities, especially trade or as a place as a rescue network and provider of employment opportunities for most people in District VII Koto Sungai Ariak.